The Effectiveness of Using Microsoft PowerPoint Media on Learning Achievement of Indonesian Subjects Reviewed From Learning Facilities at the Home of Class V Students - Rakhmad, Rakhmad; Pratiwi, Cerianing Putri; Maruti, Endang Sri (International Journal of Technology and Education Research, 2025)
There is still a lack of use of learning media and teachers still play a role as a learning center, resulting in students becoming bored in participating in teaching and learning activities. This is because students only hear explanations from the teacher. This also results in students becoming passive so that interest in lessons decreases. Based on this background, this study was conducted with the aim of determining the effectiveness of the use of Microsoft PowerPoint media on the learning achievement of Indonesian class V reviewed from home learning facilities. From the results of the two-way anava analysis, it shows (1) Ho is rejected so that it can be concluded that there is an influence of the use of Microsoft PowerPoint learning media in improving the learning achievement of grade V elementary school students; (2) Ho denied that home learning facilities have an influence on the achievement of student learning achievement; (3) Ho accepted that there was no interaction between Microsoft PowerPoint learning media and home learning facilities on the Indonesian learning achievement of grade V elementary school students.